Validation of clinical prognostic scores for patients treated with curative‐intent for recurrent colorectal liver metastases. Issue 6 (8th January 2018) - Dupré, Aurélien; Rehman, Adeeb; Jones, Robert P.; Parker, Alex; Diaz‐Nieto, Rafael; Fenwick, Stephen W.; Poston, Graeme J.; Malik, Hassan Z.
Abstract : Background: Scoring systems were developed to stratify patients with colorectal liver metastases considered for liver resection into different risk groups. Such scores have never been evaluated in recurrent liver metastases. The aim of this study was to evaluate whether these scores are applicable to patients with recurrent colorectal liver metastases and treated with curative intent. Methods: We retrospectively analyzed data from 375 consecutive patients who underwent liver surgery for colorectal liver metastases between June 2010 and August 2015. Seventy‐three patients developed liver‐limited recurrence treated with curative intent. The predictive value of 6 scores (Fong, Sofocleous, Nagashima, Nordlinger, Konopke, and the Basingstoke index) was assessed in this set of patients. Results: Median follow‐up was 36.2 months. Overall survival and progression‐free survival were 33.6 and 5.6 months, respectively. When scores were applied for OS, none showed a significant stratification between patients, although Nagashima's score showed a significant difference in overall survival between patients from the low‐risk group and those from the intermediate‐ and high‐risk groups (40.8 vs 30.5 months, P = 0.039). For PFS, only Fong's score showed a statistically significant stratification (6.6 vs 4.7 months, P = 0.027). Conclusion: Scoring systems are of limited‐value in stratifying patients operated on for recurrent colorectal liver metastases.